Pilot Testing for Feasibility in a Study of Student Retention and Attrition in Online Undergraduate Programs - Fraser, Joy; Fahlman, Dorothy (Willy); Arscott, Jane; Guillot, Isabelle (International Review of Research in Open and Distributed Learning, 2018)
Prior to undertaking a descriptive study on attrition and retention of students in two online undergraduate health administration and human service programs, a pilot test was conducted to assess the procedures for participant recruitment, usability of the survey questionnaire, and data collection processes.  A retention model provided the conceptual framework for this investigation to identify and organize various factors that influenced students’ decisions to either discontinue or continue their educational programs.  In an attempt to contribute to the body of research in this area and to enrich pedagogical practices, the authors describe the pilot testing processes and feasibility issues explored, and the improvements made to the instrument and methodology before commencing the main research study on attrition and retention.